EFEKTIVITAS MODEL PEMBELAJARAN STEM DAN PROJECT-BASED LEARNING DALAM MENINGKATKAN PEMAHAMAN IPA DI SD - Alfia Habwah Hendranti; Bunga Aldenina; Tristia Layla Indriani; Sofyan Iskandar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Science is an essential subject in elementary school, as it plays a significant role in developing scientific thinking, curiosity, and students' ability to understand natural phenomena logically and systematically. However, in practice, many students face difficulties in grasping scientific concepts. The aim of this study is to examine the effectiveness of implementing STEM and Project-Based Learning (PjBL) models in enhancing students’ conceptual understanding and learning motivation. The research method employed is a systematic literature review of various relevant previous studies. The findings indicate that the application of STEM and PjBL learning models can improve elementary students’ understanding of science concepts, creativity, and critical thinking skills.